MANAJEMEN KURIKULUM BERBASIS KERANGKA KUALIFIKASI NASIONAL INDONESIA (KKNI) DI PERGURUAN TINGGI ISLAM - Adlan Fauzi Lubis (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2020)
The purpose of this study was to analyze planning, implementation, and evaluation of curriculum development based on Indonesian National Qualification Framework (KKNI) in the Islamic Education Department at Muhammadiyah University, Jakarta. This research uses qualitative approach. Interviews were conducted directly with informants consisting of the Dean, Vice Dean, Head of Islamic Education Department. The results of observations and documentation were obtained from various studies of documents, manuscripts, and archives related to the KKNI-based curriculum management. Data analysis is based on data reduction, data display, and verification. The result of this study figures out that: a) The curriculum of the Islamic Education Department at UMY has been approved in accordance with the KKNI curriculum and each components of curriculum management consist of planning, implementing, and evaluating of the curriculum although there are deficiencies in each process; b) The development of curriculum management needs attention to Standard Operational Procedures and curriculum arrangements for the KKNI although its implementation is not entirely based on the KKNI.